Outbreak of Orthotomicus erosus (Coleoptera, Curculionidae) on Aleppo Pine in the Mediterranean Region in Croatia - Milan Pernek; Nikola Lacković; Ivan Lukić; Nikola Zorić; Dinka Matošević (South-East European Forestry, 2019)
Background and Purpose: Orthotomicus erosus, Mediterranean pine engraver, is widely distributed across the Mediterranean and southern Europe, Asia and North Africa. It is considered as secondary pest found on recently dead or felled trees, but can also attack weakened living trees. In high population levels this species can attack healthy trees and cause their dieback. Severe outbreaks occur after dry periods, or after fire in adjoining stands in warmer parts of the Mediterranean region, while this scenario has never happened in Croatia up to now. Bark beetles are important forest pests which have already been researched and discussed in relation to climate change, indicating that the predicted increase in temperature would lead to higher survival rates and faster development, thus directly influencing their population dynamics. Increase in temperature may stimulate changes in insects’ rate of development, voltinism, population density, size, genetic composition, extent of host plant exploitation, longitudinal and latitudinal distribution. Since climate conditions might have changed in the last few years as predicted in the Mediterranean region, the aim of our research is to document the first outbreak with high population levels of O. erosus in Croatia. Materials and Methods: The extent of dieback was evaluated by counting trees with dieback symptoms on diagonal transects plotted through each of 33 forest management sections of Marjan Forest Park (Split). Trunk sections from several trees with early stage symptoms were collected for further laboratory analysis, which consisted of incubation phase and subsequent morphological identification. During regular yearly surveys in forests of Croatia, the pest was observed on several sites and damages were recorded for both years 2017 and 2018. The records were entered into a map using QGIS version 3.2.1-Bonn. Spatial data was downloaded from DIVA-GIS server. Monitoring efforts were initiated in affected areas where 13 flight barrier pheromone traps (Theyson®) equipped with pheromone lure Erosowit® (Witasek, Austria) were set-up in late March in state-owned and privately owned forests across Dalmatia. Catches in the traps were collected and O. erosus adults were counted on a weekly basis in order to identify the abundance of the pest in monitored sites, as well as to obtain the first information about population dynamics and to assess voltinism. Results: On-site survey and the evaluation of dieback extent included sampling of 5% of all trees in Marjan Forest Park ,and the results showed that 23% of all trees in the forest park were affected by dieback symptoms. Visual examination of trunks, branches and bark showed symptoms of bark beetle infestation, while preliminary on-site examination of the observed adults pointed out to O. erosus. After two weeks in controlled conditions, bark beetle adults started to emerge from trunk sections which were placed in several mesh cages for incubation. Morphological identification by using stereomicroscope and the key for European bark beetles resulted in identification of O. erosus species. Over the course of the year 2017 one more site was reported to be infested with O. erosus, and eight additional sites were reported over the course of year 2018. In total, 446 ha were reported as infested, varying in intensity, in several different management units of state-owned and privately owned forests. The total number of trapped beetles in pheromone traps varied largely among sites. Our data indicate that several generations (at least 5 generations per year) were present in the year 2018. Conclusions: Sudden surge in observed damages, as well as the number of beetles trapped during monitoring, in years 2017 and 2018 throughout Aleppo pine forests in Dalmatia are the first record of O. erosus outbreak in Croatia. O. erosus is native to Croatia and so far it has been considered only as a minor pest whose outbreaks have never been recorded. Drought intensity and frequency and aridification trends in the research area (Dalmatia, Croatia) cause cumulative stress to trees and have increased O. erosus occurrence. O. erosus is expected to exhibit increased voltinism, better overwintering performance and earlier spring flights. Our first results confirm this epidemic stage of O. erosus with high abundances in Dalmatia in 2018 and at least 5 generations per year, which alter the population level of this pest. Finally, with high dispersal abilities of O. erosus through active flight and easy transportation with infested material (logs and branches with bark), O. erosus has the potential to become an important forest pest in Croatia. Thus, extensive studies on its biology, ecology, natural enemies and interaction with ophiostomatoid fungal species are needed in order to predict further spread and suggest viable and effective management measures.